2001
DOI: 10.1002/clc.4960240207
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of acute pulmonary thromboembolism in Japan: Results of a multicenter registry in the japanese society of pulmonary embolism research

Abstract: SummaryBackground: Although the incidence of acute pulmonary thromboembolism (APTE) has been increasing in Japan, patient characteristics, management strategies, and outcome

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
108
11
9

Year Published

2004
2004
2010
2010

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 159 publications
(146 citation statements)
references
References 20 publications
18
108
11
9
Order By: Relevance
“…PE Perfusion MRI index was 85.0%. 533 patients with PE reported in-hospital mortality rate of 14.0% (37). Our mortality rate of 16% can thus be considered to be comparable.…”
Section: Discussionsupporting
confidence: 57%
“…PE Perfusion MRI index was 85.0%. 533 patients with PE reported in-hospital mortality rate of 14.0% (37). Our mortality rate of 16% can thus be considered to be comparable.…”
Section: Discussionsupporting
confidence: 57%
“…These findings were consistent with the characteristics of Japanese patients reported earlier. 4,5,19 When the clinical characteristics were compared between the DVT-positive patients and the DVT-negative patients, there was no statistically significant difference (Table 1).…”
Section: Resultsmentioning
confidence: 96%
“…12 In addition, several risk factors for CTEPH have been identified, including chronic inflammatory disorders, myeloproliferative syndromes and splenectomy. 4,13 These observations implied that inflammatory or immune-related mechanisms might be involved in the pathogenesis of CTEPH. In accordance with this hypothesis, HLA analyses had been done in patients with primary pulmonary hypertension, and it was reported that certain types of HLA antigens or HLA alleles, such as HLA-B35, -DR3, -DR6, -DR52, -DQ2 and -DQ7, were associated with the disease in Caucasoid populations.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations